2018
DOI: 10.1177/1049732318814540
|View full text |Cite
|
Sign up to set email alerts
|

An Ecocultural Perspective on Eating-Related Routines Among Low-Income Families With Preschool-Aged Children

Abstract: Eating-related routines, such as regular mealtimes, can protect against obesity. Little is known about eating-related routines among preschoolers or the factors that shape those routines. Ecocultural Theory and qualitative interviews with 30 caregivers of preschoolers in Colorado were used to describe eating-related routines at home and parents’ perspectives on the factors that shape routines. Qualitative content analysis was used to analyze and interpret data. Consistent with clinical recommendations, parents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 53 publications
(62 reference statements)
0
17
1
Order By: Relevance
“…The similarity in plate waste across food categories is inconsistent with eating behaviours, such as food refusal and picky eating, that predictably emerge during the preschool years and are pervasive among young children . In the United States, parents have reported that preschoolers consume a limited variety of foods and prefer some food types over others; however, those parent perceptions are not supported by findings from current study. One possible explanation for what appears to be a lack of selective eating is that parents served larger portions of foods they thought their preschoolers would eat.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…The similarity in plate waste across food categories is inconsistent with eating behaviours, such as food refusal and picky eating, that predictably emerge during the preschool years and are pervasive among young children . In the United States, parents have reported that preschoolers consume a limited variety of foods and prefer some food types over others; however, those parent perceptions are not supported by findings from current study. One possible explanation for what appears to be a lack of selective eating is that parents served larger portions of foods they thought their preschoolers would eat.…”
Section: Discussioncontrasting
confidence: 82%
“…Previous work by the authors indicates that parents value good nutrition for their preschoolers, which they described as diets high in fruits and vegetables and low in sugars and fats . In other US samples, parents similarly report the importance of healthy eating for their children, especially related to obesity prevention .…”
Section: Discussionmentioning
confidence: 99%
“…Considering how to change the behavior of parents and children who do not have regular mealtimes is a complex issue. Previous study 11 findings have indicated a close relationship between children's mealtimes and their parents' working times and other lifestyle elements [22]; in this context, behavior change can be difficult. Moreover, many young children also receive foods at places outside the home, such as at nursery schools and kindergartens.…”
Section: Discussionmentioning
confidence: 94%
“…Considering how to change the behavior of parents and children who do not have regular mealtimes is a complex issue. Previous study ndings have indicated a close relationship between children's mealtimes and their parents' working times and other lifestyle elements [22]; in this context, behavior change can be di cult. Moreover, many young children also receive foods at places outside the home, such as at nursery schools and kindergartens.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, it is unknown how the participants' care of children's diets may have impacted children's physical and mental development. A number of studies have examined associations between mealtimes and the physical and mental health of children [22,31,35], and a few researchers have reported a relationship between mealtimes and food diversity [13,23]. Therefore, further research on this issue is required.…”
Section: Discussionmentioning
confidence: 99%